Alfaxalone population pharmacokinetics in the rat: Model application for pharmacokinetic and pharmacodynamic design in inbred and outbred strains and sexes. Issue 6 (15th November 2022) - White, Kate; Aldurdunji, Mohammed; Harris, John; Ortori, Catherine; Paine, Stuart
Abstract: The translation of new injectable anesthetic drugs from rodent to humans remains slow, despite the realization that reliance on the volatile agents is unsustainable from an environmental perspective. The aim of this study was to investigate the influence of rat sex and strain on the PK and PD of the anesthetic neurosteroid alfaxalone. Forty rats had cannulas inserted under isoflurane anesthesia for drug administration and sampling. Carotid artery blood samples were collected for blood gas analysis, hematology, biochemistry, and plasma concentrations of alfaxalone. Plasma samples were assayed using liquid chromatography‐mass spectrometry. Compartmental non‐linear mixed effects methods (NLME) models were applied to two rat populations to determine whether body weight, sex, and strain influenced PK parameters. There were significant differences between the sexes for plasma clearance, half‐life and mean residence time in Lewis rats, and mean arterial blood pressure was significantly lower in the female rats at 120 min. An initial NLME PK population model was used to design an adjusted alfaxalone infusion for SD females matching plasma concentrations in males and minimizing cardiopulmonary depression but maintaining an appropriate hypnotic effect. A final NLME population model showed that alfaxalone clearance was dependent on both bodyweight and sex, whereas volume of distribution was influenced by strain. NLME PK models offer the advantage of having a single model that describes a population and therefore shares data interpretation between animals unlike the standard deterministic PK approach. This approach can be used to propose bespoke dosing regimens for optimal use of alfaxalone Abstract : Alphaxalone plasma concentration‐time curves; comparison between observed/simulated male (blue squares/lines) and female (red circles/lines) in Lewis rats for the same dosing regimen: 1.67 mg/kg/min for 2.5 min followed by 0.75 mg mg/kg/min for 60 min, followed by a reduction to 0.52 mg/kg/min.